1987
DOI: 10.1111/j.1365-2125.1987.tb03093.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mixed micelles formed from glycocholic acid and lecithin with the protein binding of various drugs.

Abstract: Mixed micelles (MM) formed from glycocholic acid and lecithin are suited to solubilize lipophilic drugs for intravenous use. To test for possible drug‐drug interactions, the protein binding of a series of agents known to bind to different sites on albumin (diazepam, warfarin, ketoprofen, frusemide, probenecid) and additionally (prazosin, quinidine, propranolol) or exclusively (disopyramide) to alpha 1‐acid glycoprotein or to transcortin (prednisolone) was determined in the presence and absence of MM. Concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Alternatively, it cannot be excluded that this effect is the result of a displacement interaction caused by some (degradation) components of polysorbate 80. Similar observations have been reported for the binding of several other drugs that bind with high affinity but low capacity to AAG in the presence of structurally related mixed‐micellar systems 21 . It is interesting that the effect of polysorbate 80 appears to be biphasic both in vitro and in vivo, with a slight decrease in the f u at low concentrations of the vehicle.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Alternatively, it cannot be excluded that this effect is the result of a displacement interaction caused by some (degradation) components of polysorbate 80. Similar observations have been reported for the binding of several other drugs that bind with high affinity but low capacity to AAG in the presence of structurally related mixed‐micellar systems 21 . It is interesting that the effect of polysorbate 80 appears to be biphasic both in vitro and in vivo, with a slight decrease in the f u at low concentrations of the vehicle.…”
Section: Discussionsupporting
confidence: 80%
“…Similar observations have been reported for the binding of several other drugs that bind with high affinity but low capacity to AAG in the presence of structurally related mixedmicellar systems. 21 It is interesting that the effect of polysorbate 80 appears to be biphasic both in vitro and in vivo, with a slight decrease in the f u at low concentrations of the vehicle. The mechanism underlying this phenomenon is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lipophilic drugs are known to interact with HA38, 39 and it is possible that HA could sequester 17AAG or 17AAGH 2 in a hydrophobic interaction. The association of 17AAG and 17AAGH 2 with HA was measured by HPLC after incubation of either 17AAG or 17AAGH 2 (generated by NQO1 and NADH) with HA.…”
Section: Resultsmentioning
confidence: 99%
“…Many hydrophobic drugs can bind with HA38, 39 and HA is the primary protein in serum that binds acidic drugs 42. Previous studies using mouse models and membrane filtration suggested that >90% of 17AAG in mouse serum was protein bound 23.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bertucci [16] reported results of displacement chiral HPLC when noncovalent reversible binding of lithocholate to the second drug-binding cavity (site II) on the human serum albumin (HSA) induces an enhanced inhibition of ketoprofen, naproxen and surprofen enantioselective transport by this plasma drug carrier protein. In addition, Guentert et al [17] reported that mixed micelles formed from glycocholic acid and lecithin were well suited to solubilize ketoprofen and were preferentially bound to the plasma 1 -acid glycoprotein (AGP). However, Bielejewska et al [18] described use of the cholic acid and taurodeoxycholic acid as single and combined with native cyclodextrins (CDs) chiral selectors in HPLC and capillary electrophoresis (CE) systems which enabled highly selective enantioseparation of binaphtol atropoisomers.…”
Section: Introductionmentioning
confidence: 98%